On the evaluation of the mechanical behaviour of structural glass elements - Costa, S.
Glass can be considered to be a high-technology engineering material with a multifunctional potential for structural applications. However, the conventional approach to the use of glass is often based only on its proper-ties of transparency and isolation. It is thus highly appropriate and necessary to study the mechanical behaviour of this material and to develop adequate methods and models leading to its characterisation. It is evident that the great potential of growth for structural glass applications is an important opportunity of development for the glass industry and the building/construction sectors. The work presented in this paper is a reflection of this conclusion. The authors shortly present the state-of-the-art on the application of glass as a structural element in building and construction, and refer to other potential fields of application and available glass materials. The experimental procedures and methods adopted in three-point bending tests performed on 500 x 100 [mm(2)] float, laminated and tempered glass specimens with thicknesses between 4 and 19 mm are thoroughly described. The authors evaluated the mechanical strength and stiffness of glass for structural applications. This work contributes to a deeper knowledge of the properties of this material.